(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the impact of foreign language anxiety (FLA) on speaking performance among Libyan university EFL learners using a mixed-methods approach. Quantitative data were collected through a structured questionnaire administered to 22 undergraduate students from Yefren Faculty of Education and the University of Tripoli, while qualitative insights were obtained through document analysis. The findings reveal that anxiety exerts a moderate to high negative effect on key dimensions of speaking performance. A majority of participants reported that anxiety impairs fluency (59.1%, M = 3.73) and reduces performance despite preparation (63.7%, M = 3.73), indicating disruption in real-time language processing. Anxiety also significantly affected vocabulary recall (68.2%, M = 3.77) and caused hesitation in speaking (68.2%, M = 3.77), highlighting its strong cognitive impact. In addition, learners reported reduced confidence (M = 3.64) and increased tension during presentations (68.2%, M = 3.68), reflecting the affective dimension of anxiety. Physical symptoms such as trembling and voice instability were also observed (50%, M = 3.32), confirming its physiological influence. In contrast, anxiety showed limited effects on motivation (72.8% disagreement, M = 2.27) and class avoidance (71.4% disagreement, M = 1.95), suggesting that it primarily affects performance rather than engagement. The findings further demonstrate that anxiety has a weaker impact on grammar use (M = 2.36), reinforcing the distinction between linguistic competence and performance. Overall, the study highlights the multidimensional nature of foreign language anxiety and provides empirical evidence from an under-researched context, offering important pedagogical implications for reducing anxiety and enhancing speaking performance in EFL classrooms.